2000
DOI: 10.1177/009365000027002004
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and Evaluative Consequences of Inappropriate Leader Displays

Abstract: This study manipulated the appropriateness of presidential reactions to images of compelling news events to investigate how a political leader's nonverbal behavior evokes emotional responses and trait attributions. A repeated-measures experiment examining the combined effects of valence and arousal on viewers' affective reactions and trait evaluations was conducted on two voting-age subject pools in different states. Participants were shown a series of four news story-presidential reaction message sequences an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(88 citation statements)
references
References 39 publications
3
82
0
3
Order By: Relevance
“…At the same time, participant determination remained nearly the same from prior to until after the speech when the microexpressions were removed, but decreased markedly when the micro-expressions remained in the speech. In summary, President Bush's facial micro-expressions dampened emotional response to the semantic and nonverbal content of the speech, a finding in line with Bucy and colleagues' assessment of the impact of inappropriate facial displays (Bucy 2000(Bucy , 2003Bucy and Bradley 2004;Bucy and Newhagen 1999).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…At the same time, participant determination remained nearly the same from prior to until after the speech when the microexpressions were removed, but decreased markedly when the micro-expressions remained in the speech. In summary, President Bush's facial micro-expressions dampened emotional response to the semantic and nonverbal content of the speech, a finding in line with Bucy and colleagues' assessment of the impact of inappropriate facial displays (Bucy 2000(Bucy , 2003Bucy and Bradley 2004;Bucy and Newhagen 1999).…”
Section: Discussionsupporting
confidence: 75%
“…Leaders who are capable of expressing a range of emotions may be more effective in gaining support and empathy in a process of communication where emotional response by viewers of a speech plays a key role. Here, we find that congruence of expressions with the message presented plays a highly important role in viewer response (Bucy 2000(Bucy , 2003 Fig. 3 Change in reported feelings of being determined 1999).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…According to Bono & Illies (2006), a leader's use of negative emotion in his/her rhetoric is a powerful tool given that it has stronger and longer effects on followers than positive emotion. Moreover, as indicated by Bucy (2000), followers may evaluate negative displays of emotion as more honest, trustworthy, and credible than positive displays. In some instances, followers may even perceive a leader's display of negative emotion such as anger to be indicative of the leader's competence (Glaso & Einsaren, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…According to these researchers, leaders' positive affect arouses positive emotion in followers, which in turn results in positive mood. However, several researchers have also shown that the effects of affect are contextdependent, with negative affect being rated more favorably than positive affect in particular situations (Bucy, 2000;Bono & Illies, 2006;Damen et al, 2008;Glaso & Einsaren, 2008). Damen et al (2008) found that the display of positive or negative affect mainly depended on its perceived appropriateness.…”
Section: Charismatic Rhetoric and Affective Languagementioning
confidence: 99%